Protection of Short Transmission Lines Using Microprocessor-Based Distance Relay - Mohammed Ali, Hussain Fadhil (2004)
Distance protection is used for the protection of transmission or sub-transmission lines, usually 33 KV, 66 KV and 132 KV lines. A distance relay measures the distance between the relay location and the point of fault in terms of impedance, reactance, etc. An mpedance relay measures the line impedance between the fault point and relay location; a reactance relay measures reactance, and mho relay measures a component of admittance. With advances in technology, protective relays have progressed from electromechanical, to solid state to microprocessor-based relays. The increased growth of power systems both in size and complexity has brought about the need for fast and reliable relays to protect major equipment and to maintain system stability. With the development of economical, powerful and sophisticated microprocessors, there is a growing interest in developing microprocessor-based protective relays which are more flexible because of being programmable and are superior to conventional electromagnetic and static relays. The main features which have encouraged the design and development of microprocessor-based protective relays are their economy, compactness, reliability,flexibility and improved performance over conventional relays. The distance relays are preferred to over current relays because they are not nearly so much affected by changes in short-circuit-current magnitude as over current relays are, and, hence are much less affected by changes in generating capacity and in system configuration. This is because distance relays achieve selectivity on the basis of impedance rather than current. This thesis presents the design and operation technique for protection of short transmission lines using microprocessor-based distance relay. The characteristics of a distance relay is realised by comparing voltage and current at the relay location. The ratio of voltage (V) to current (I) gives the impedance of the line section between the relay location and the fault point. The signal will be taken from the transmission line and it will be converted to digital signal then goes to the microprocessor which has a program written in assembly language to estimate the resistance of the protected line, then the decision will be made according to this signal whether it is a fault signal or otherwise, and identify the faulty phases. The faults that have been tested are phase faults and the results have been indicated by giving the indication of the faulty phase at the same time giving signal to trip and isolate the faulty area. Different tests have been made successfully. The thesis presents one of these tests made practically